Analysis of metronidazole removal and micro-toxicity in photolytic systems: Effects of persulfate dosage, anions and reactor operation-mode. Issue 1 (February 2018) - Neghi, N.; Krishnan, Navneeth R.; Kumar, Mathava
Graphical abstract: Highlights: UV/PS/TiO2 system showed faster degradation kinetics compared to PS and UV/PS systems. MNZ removal in UV-C/PS system accelerated in presence of SO4 2− . Presence of NO3 − and Cl − reduced the MNZ removal efficiency in the initial phase. Performance of BPR and CPR evaluated by energy consumption and EEO analysis. Micro-toxicity of final treated effluent was within the toxic limits in UV/PS system. Abstract: The efficiency of persulfate (PS) alone, UV-C activated TiO2 (UV/TiO2 ), UV-C activated PS (UV/PS) and UV/PS with TiO2 (UV/PS/TiO2 ) in the oxidative removal of metronidazole (MNZ) was studied. In addition, applicability of UV/PS process in batch and continuous photo-reactors (BPR and CPR) was investigated. The performance of BPR and CPR was assessed in terms of energy consumed and electrical energy per order (EEO ), which indicated that both UV/PS and UV/PS/TiO2 systems were energy efficient. On the other hand, MNZ removal kinetics has revealed a higher MNZ removal rate of 0.232 min −1 in UV/PS/TiO2 system and showed a pseudo-first-order kinetics (r 2 > 0.96). Furthermore, the effect of influent anion concentration (i.e. Cl −, SO4 2−, NO3 − and their combinations) on UV/PS system was examined. The sequence of MNZ removal (from highest to lowest) in the presence of anions was (SO4 2− + Cl − + NO3 − ) > (SO4 2− + NO3 − ) > SO4 2− > (SO4 2− + Cl − ) > Cl − > NO3 − . An oxidative degradation pathway of MNZ in UV/TiO2 system was proposed. The toxicity of treated samples was evaluated using micro-toxicity assay against V. fischeri . The percentage inhibition of effluent samples to V. fischeri was within 15%, which denotes the suitability of CPR for real-time application.